Respuesta :

Answer:

Choice C is the correct solution

Step-by-step explanation:

We can split up the terms under the cube root sign to obtain;

[tex]\sqrt[3]{32}*\sqrt[3]{x^{8} }*\sqrt[3]{y^{10} }\\\\\sqrt[3]{32}=\sqrt[3]{8*4}=\sqrt[3]{8}*\sqrt[3]{4}=2\sqrt[3]{4}\\\\\sqrt[3]{x^{8} }=\sqrt[3]{x^{6}*x^{2}}=\sqrt[3]{x^{6} }*\sqrt[3]{x^{2} }=x^{2}*\sqrt[3]{x^{2} }\\\\\sqrt[3]{y^{10} }=\sqrt[3]{y^{9}*y }=\sqrt[3]{y^{9} }*\sqrt[3]{y}=y^{3}*\sqrt[3]{y}[/tex]

The final step is to combine these terms;

[tex]2\sqrt[3]{4}*x^{2}*\sqrt[3]{x^{2} }*y^{3}*\sqrt[3]{y}\\\\2x^{2}y^{3}\sqrt[3]{4x^{2}y }[/tex]